THE IMPROVEMENT OF OBSERVATION REPORT WRITING SKILL THROUGH THE APPLICATION OF EXPERIENTIAL LEARNING MODEL (CLASSROOM ACTION RESEARCH IN THE FIFTH GRADE STUDENTS OF SURAKARTA STATE PRIMARY SCHOOL AT 2017/2018 ACADEMIC YEAR - Sulistya Ardiani Ardiani Kusumastuti; Yulianti Yulianti; Endang Sri Markamah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this research is to improve the observation report writing skill by applying Experiential Learning model. This form of research is a classroom action research conducted two cycles. Each cycles consist of two times and each times consist of four phases, they are planning, action, observation, and reflection. The data collecting technique are interview, observation, documentation, and test. The data validity technique og the research is content validity. The data analysis technique is interactive analysis model (Mile & Huberman). The result of this research, shows that the application of Experiential Learning models that can improve the observation report writing skill. Applying Experiential Learning model appropritate with the teoritical study that the has been done for twi cycles could improve the skill of observation report writing skill by applying Experiential Learning model on the fifth grade students of Tegalsari No.60 Surakarta state primary school at 2017/2018 academic year.